Penentuan Umur Simpan dan Pengembangan Model Diseminasi dalam rangka Percepatan Adopsi Teknologi Mi Jagung bagi UKM - Nurheni Sri Palupi; Feri Kusnandar; Dede Robiatul Adawiyah; Dahrul Syah (Institut Pertanian Bogor, 2010)
Technology of corn noodle, both processed from 100% corn flour and substitution of wheat flour (by corn flour), was developed by previous researchers but it has not been tested to be applied to the community. The objectives of this study were: (1) identify critical quality parameters and determine the shelf life of corn noodle; (2) to test the production process of dry- and wet-corn on a pilot plant scale and the small industry of wet noodles; and (3) to obtain the quantitative data of consumer acceptance from the wet noodle producers (small-medium enterprise or SMEs) and the consumers. The critical parameters of corn noodles quality during storage were the color, texture (ease of fracture), cooking loss (loss of solids due to cooking), and the degree of rancidity. Based on the aroma parameters, the shelf life of corn noodles on the storage temperature reaches 28oC was 4.6 months. Production of corn noodle routinely has been performed in a pilot plant of SEAFAST Center with a capacity 4 batch per day process. According to the wet noodles producers (small industry), the technology of the 35% substitution of corn noodles (wet noodle) can be directly adopted by SMEs without any change in the production process. The technology of 100% corn noodles can also be adopted with the addition of blanching units before sheeting process. The respondents accept the 35% substitution of corn noodles and considered no different than wheat noodles. Eighty-five percents of meatball noodles SMEs stated that are willing to use the corn wet noodle. Eighty percents of consumer’s meatball noodle said that the wet corn noodle were suitable using for meatball noodles with the acceptance value were close to the wheat noodles.